1991
DOI: 10.1038/bjc.1991.474
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with chlorins for diffuse malignant mesothelioma: initial clinical results

Abstract: Summary Four patients underwent intraoperative photodynamic therapy after surgery with meso-tetra-(hydroxyphenyl)-chlorin (mTHPC-PDT) for diffuse malignant mesothelioma. Preliminary procedures were performed in two patients in order to establish the efficacy of mTHPC-PDT and to optimise its tumoricidal effect. The (Faber, 1988). Improved local control does require additional measures, but the disease responds poorly to radio-and chemotherapy (Lerner et al., 1983). As photodynamic therapy (PDT) has been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
118
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(123 citation statements)
references
References 11 publications
5
118
0
Order By: Relevance
“…Besides their effectiveness in PDT treatments, poor selectivity for diseased tissues, high dose, extended retention in the host organism, and low wavelength activation (630 nm) were the main drawbacks (7,14). These drawbacks stimulated the development of new PSs showing fast elimination from the body, fewer side effects, and a higher absorption peak (650-800 nm) (6,7,15).…”
Section: Photosensitizer Liposome Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides their effectiveness in PDT treatments, poor selectivity for diseased tissues, high dose, extended retention in the host organism, and low wavelength activation (630 nm) were the main drawbacks (7,14). These drawbacks stimulated the development of new PSs showing fast elimination from the body, fewer side effects, and a higher absorption peak (650-800 nm) (6,7,15).…”
Section: Photosensitizer Liposome Formulationsmentioning
confidence: 99%
“…Despite the improvements achieved, these molecules present low solubility in physiological solutions (6,7,15). For instance, both phthalocyanines and chlorins are hydrophobic PSs that form aggregates in physiological solutions (16).…”
Section: Photosensitizer Liposome Formulationsmentioning
confidence: 99%
“…This results in a depth of light penetration of at least 1 cm and high tumor selectivity. Light with a wavelength longer than 850 nm is not used due its weak energy which is not enough to initiate a photochemical reaction [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to differential drug levels in tumour vs normal tissue at 2 -4 days after injection. Early clinical data in mesothelioma patients also demonstrated good selectivity, with drug concentrations in the tumour of 5 -14 times that in surrounding normal tissue (pulmonary artery, bronchus, muscle and skin) at 2 -3 days after drug administration (Ris et al, 1991;Braichotte et al, 1992). A study of PDT for metastatic gynaecological cancer (Wierrani et al, 1997) also demonstrated concentration ratios of 3 -6 for tumour/ fatty tissue (retroperitoneal pelvic wall area) in a series of patients biopsied at 4 days after Foscan.…”
mentioning
confidence: 99%